Innovation and Industrial Espionage in Eighteenth-Century France: An Investigation of the Selling of Silks through Samples. - Miller, Lesley Ellis (Journal of Design History, 1999)
Although there is a considerable literature on the pre-eminence of French patterned silks in the fashion markets of eighteenth-century Europe, there is little consideration of the processes by which interest in these products was maintained season after season in the face of competition from an increasing number of manufactories. This article addresses this omission, by concentrating on one particular selling practice of the Lyons silk industry, that of selling by samples. It charts the transformation in manufacturers' perception of samples from useful marketing tools into dangerous sources of information for illegitimate imitators.